Testing Nordmore grids on the target and by-catch species of the commercial bottom trawl fishery in the Gulf of Cadiz - Gamaza, MariÁngeles (2016)
Sorting grids have been tested worldwide in trawl fisheries. Here we report upon the first trials performed using Nordmore sorting grids with four different bar spacings in the trawl fisheries of the Gulf of Cadiz targeting crustaceans as the main resource. A total of 288 valid hauls and 67 commercial species were caught. Escapement and escape size selectivity were evaluated for the most important target and by-catch species. A decrease in the percentage of biomass escape was recorded with increasing grid spacing for the two target species, deep-water rose shrimp (Parapenaeus longirostris) and Norway lobster (Nephrops norvegicus), from 24% to 8% for the former and from 86 to 9% for the latter, with a 15-mm and 30-mm grid respectively. In general, high escape rates were found for most finfish and cephalopods. For hake (Merluccius merluccius), as the main by-catch species, the results showed an escape rate decreasing from 96% to 71% as the bar spacing increased. Our findings suggest the 30-mm grid would be effective for the deep-water crustacean trawlers but different mitigation measures will be required for other metiers in the multispecies trawl fishery of the Gulf of Cadiz.